Penggunaan koping pet attachment untuk mengatasi stress akademik pada mahasiswa - Rahmi Imelisa; Aurora Nur Ainun Syafira Sarja; Ibrahim Noch Bolla (JOURNAL OF Mental Health Concerns, 2023)
Background: Most of the early adult age range, carry out their activities as a college students. As a student, a lot of stress occurs related to the learning process at college, this is known as academic stress. To overcome this, an appropriate coping mechanism is needed. Raising a pet (pet attachment) could be use as a coping strategy to deal with academic stress. Purpose: This research aimed to determine the relation between pet attachment coping strategies and student academic stress at a college in Cimahi city. Method: This study used a quantitative analytical survey method and cross-sectional design. Respondents were selected by purposive sampling technique as many as 89 students. Data analysis consisted of univariate analysis and bivariate analysis using the chi-square test. Results: Based on data analysis, it was found that 53,9% of students had a moderate levels of academic stress, and 66,3% had a high attachment to pets. The bivariate test showed a p-value of 0,0006 (< α=0,05). Conclusion:There is a relation between pet attachment coping strategies and academic stress in the college students. Suggestion: It was suggested that the students use this coping strategies to cope with academic stress.   Keywords:  Stress; Academic; Student; Pets; Cross-Sectional.   Pendahuluan: Pada rentang usia dewasa awal, sebagian besar individu menjalani aktivitasnya sebagai seorang mahasiswa. Sebagai mahasiswa stress yang banyak terjadi berkaitan dengan proses pembelajaran di kampusnya, hal tersebut dikenal dengan istilah stress akademik. Untuk mengatasi hal tersebut, diperlukan mekanisme koping yang sesuai. Memelihara hewan peliharaan (pet attachment) dapat menjadi salah satu strategi koping untuk mengatasi stress akademik. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan strategi koping kelekatan dengan hewan peliharaan(pet attachment)dengan stres akademik mah asiswa di salah satu perguruan tinggi di Kota Cimahi. Metode: Penelitian ini menggunakan metode kuantitatif survey analitik dengan rancangan cross sectional.Responden penelitian dipilih dengan teknik purposive samplingsebanyak 89 mahasiswa. Analisa data terdiri dari analisa univariat dan analisa bivariat menggunakan uji chi-square. Hasil: Berdasarkan analisa data didapatkan 53,9% mahasiswa memiliki tingkat stres akademik sedang, dan 66,3% memiliki kelekatan hewan peliharaan yang tinggi. Uji bivariat menunjukkan hasil p-value sebesar 0,006 (< α=0.05). Simpulan: Aada hubungan antara strategi koping pet attachment dengan stres akademik pada mahasiswa. Saran: Diharapkan bagi mahasiswa untuk mengaplikasikan strategi koping ini untuk mengatasi stress akademik.